Banksia Ashbyi-engineered facile green synthesis of magnetite nanoparticles: Characterization, and determination of micro-strain, stress, and physical parameters by X-ray-based Williamson-Hall analysis - Gérrard Eddy Jai Poinern; A F M Fahad Halim; Derek Fawcett; Peter Chapman; Rupam Sharma (AIMS Materials Science)
Magnetite nanoparticles (MNPs) were synthesized by a straightforward one-step biogenic process using a leaf extract taken from the Australian indigenous plant Banksia ashbyi (BA). Several advanced characterization techniques, such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), energy-dispersive spectroscopy (EDS), thermogravimetric analysis (TGA), and Raman spectroscopy were used to investigate the physical and chemical properties of synthesized MNPs. In addition, the size and morphology of the synthesized particles were examined using both focused ion beam scanning electron microscopy (FIBSEM) and transmission electron microscopy (TEM) methods. FT-IR analysis revealed the presence of a Fe–O band located at 551 cm-1, which confirmed the formation of BA-MNPs. Both FIBSEM and TEM image analysis confirmed the nanoparticles were spherical in shape and had a mean diameter of 18 nm with a particle distribution that ranged between 13 and 23 nm. The strong iron (Fe) and oxygen (O) peaks seen in the EDS analysis also confirmed the formation of the MNPs. TGA analysis revealed the leaf extract not only acted as the reducing agent but also served as a capping agent. The XRD analysis revealed that the synthesized MNPs exhibited a high degree of crystallinity and did not contain any impurities. Furthermore, X-ray peak profile analysis using Williamson-Hall methods found the average crystallite size was 9.13 nm, with the crystal lattice experiencing a compressive stress of 546.5 MPa and an average micro-strain of 2.54 × 10-3. In addition, other material properties such as density (5.260 kg/m3), average Young's modulus of elasticity (217 GPa), modulus of rigidity (90 GPa), and Poisson's ratio (0.235) were also estimated from the XRD data.